Let F be a field
Let f(x),g(x) be polynomials of F[x] where g(x) ≠ 0
Then:
There exists unique polynomials q(x), r(x) in F[x] such that f(x) = g(x)q(x) - r(x) and r(x)=0 or deg r(x) is less than deg g(x)
Proof:
(1) Let f(x),g(x) be two polynomials such that g(x) ≠ 0
(2) We can assume that deg f(x) ≥ deg g(x) since:
if deg f(x) = 0, then f(x) = g(x)(0) - 0.
if deg f(x) is less than deg g(x), then f(x) = g(x)(0) - [-f(x)]
(3) Let:
f(x) = anxn + ... + a0
g(x) = bmxm + ... + b0
where an and bm are nonzero.
[We can make this assumption since g(x) ≠ 0 and deg f(x) ≥ deg g(x).]
(4) I will use induction to establish the existence of q(x), r(x).
(5) q(x),r(x) exist if deg f(x) = 0 since:
(a) Assume deg f(x) = 0
(b) Then there exists C such that f(x)=C
(c) Since deg f(x) ≥ deg g(x), it follows that deg g(x)= 0 and there exists D such that g(x)=D
(d) Let q(x) = C/D
(e) Then it follows that f(x) = g(x)*q(x) - 0
(6) Assume that our assumption holds true up to deg f(x) = n-1
(7) Let:
f1(x) = f(x) - anbm-1xn-mg(x)
(8) So, deg f1(x) is less than deg f(x)
(9) By the induction hypothesis, there exists q1(x) and r1(x) such that:
f1(x) = q1(x)g(x) - r1(x)
where deg r1 is less than deg g(x) or deg r1(x) = 0
(10) So, then:
f1(x) + anbm-1xn-mg(x) = anbm-1xn-mg(x) + q1(x)g(x) - r1(x)
= [anbm-1xn-m + q1(x)]g(x) - r1(x)
where deg r1 is less than deg g(x) or deg r1(x) = 0
(11) This proves the first part of the theorem. To complete it, we need to prove uniqueness.
(12) Assume that:
f(x) = g(x)q(x) - r(x) = g(x)q'(x) - r'(x)
where deg r(x), deg r'(x) = 0 or is less then deg g(x)
(13) So that:
0 = g(x)q(x) - r(x) - g(x)q'(x) + r'(x)
(14) Then:
r(x) - r'(x) = g(x)[q(x) - q'(x)]
(15) Assume that q(x) - q'(x) is nonzero.
(16) Then, deg g(x)[q(x)-q'(x)] = deg g(x) + deg (q(x) - q'(x)) [See Lemma 2, here]
(17) And, deg(r(x) - r'(x)) ≤ max(deg r(x),deg r'(x)) [See Lemma 1, here]
(18) But this is impossible since deg(r(x)) is less than deg g(x)
(19) So, we have a contradiction and we reject our assumption in step #15.
(20) So, if q(x) - q'(x) is 0, then it follows that r(x) - r'(x) is also 0.
(21) Then q(x) = q'(x) and r(x) = r'(x)
QED
Reference
- Joseph A. Gallian, Contemporary Abstract Algebra.
No comments :
Post a Comment